2004
DOI: 10.1212/01.wnl.0000133122.14824.25
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of a screening tool for Parkinson disease surgical candidates

Abstract: As there is currently no standardized assessment tool for evaluating Parkinson disease (PD) patients for deep brain stimulation (DBS), the authors developed the Florida Surgical Questionnaire for Parkinson Disease (FLASQ-PD). Part I of the study was a retrospective analysis of 174 patients presenting for a surgical screening. Part II was a multicenter study to assess the correlation of FLASQ-PD scores. The results of this study suggest that the FLASQ-PD may be a useful triage tool for screening PD patients for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 6 publications
1
54
1
1
Order By: Relevance
“…For general (community) neurologists, it may be difficult to identify patients who could be good candidates for DBS and may be referred to a specialised centre for further evaluation. In a recent US centre review [15], 63 % of patients referred were refused for DBS which underlines the necessity of adequate pre-selection. Conversely, under-referral may also exist, withholding appropriate candidates the opportunity of being assessed by a specialised movement disorder centre.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For general (community) neurologists, it may be difficult to identify patients who could be good candidates for DBS and may be referred to a specialised centre for further evaluation. In a recent US centre review [15], 63 % of patients referred were refused for DBS which underlines the necessity of adequate pre-selection. Conversely, under-referral may also exist, withholding appropriate candidates the opportunity of being assessed by a specialised movement disorder centre.…”
Section: Introductionmentioning
confidence: 99%
“…In order to support appropriate referral, Okun et al developed a screening tool (printed checklist) for DBS candidates [15]. Although an initial validation of this tool showed favourable results, its application in daily practice may be too complex and time-consuming for community neurologists.…”
Section: Introductionmentioning
confidence: 99%
“…The tool was used on a group of PD patients who had under gone interdisciplinary evaluation at a single DBS center in order to determine the validity of this screening questionnaire. The study found a significant correlation between the FLASQ-PD scores recorded and the ultimate decision of the DBS interdisciplinary team [41]. In another study, Moro et al [42] used the RAND method to evaluate surgical candidacy.…”
Section: Florida Surgical Questionnaire-pd and Rand Methods For Screementioning
confidence: 95%
“…It is important to make a distinction between idiopathic PD and atypical parkinsonism that is seen in other neurologic disorders, such as progressive supranuclear palsy and corticobasal degeneration. In idiopathic PD, dopaminergic therapy and DBS are generally effective, while in the atypical syndromes they are not [54][55][56]. The severity of PD at a given time point is quantified using measures such as the Unified PD Rating Scale (UPDRS), which includes both patient reported and The DBS lead has been placed into the right thalamus, and the patient is being asked to trace a spiral on a clipboard.…”
Section: Pdmentioning
confidence: 99%